Prevalence and genetic analyses of selected age-related macular degeneration-related polymorphisms and their responses to intravitreal ranibizumab - Mohamad, Nur Afiqah (2018)
Age-related macular degeneration (AMD), a leading cause of vision loss among elderly people is a progressive chronic disease of the central retina associated with environmental and genetic factors. Studies reported that gene polymorphism of various genes were analysed among AMD subjects from different populations with conflicting results. Among those, complement factor, vascular endothelial growth factor (VEGF), high temperature requirement A1 (HTRA1) and age-related maculopathy susceptibility 2 (ARMS2) genes were studied extensively among AMD subjects. In Malaysia the data on intravitreal ranibizumab drug therapy and the genetic association of gene polymorphisms among AMD remains unclear. The current study was initiated to determine the genetic association between the candidate gene polymorphisms in response to ranibizumab and also, the prevalence and changes in treatment patterns of ranibizumab and photodynamic therapy (PDT) among retinal eye disease patients from a tertiary care hospital. Upon ethical approval and consent, a total of 149 AMD and 152 controls were recruited for the prospective study. Moreover, a total number of 821 subjects were recruited for retrospective study using Electronic Medical Record database software from Hospital Selayang, Selangor. Genomic DNA and total RNA were extracted and the genotyping were analyzed using the conventional PCR and PCR-RFLP methods. The gene expression analysis was also performed for ARMS2 and HTRA1 genes. The statistical analysis was performed and all the data were analysed with the level of significance was set at P < 0.05. The mean age of AMD subjects were 68.6 ± 8.47 and 64.8 ± 10.21 years for the controls. Males were frequent in both AMD (64%) and controls (74%) compared to females. Among AMD, Chinese (57%) were high compared to Malays (34%) and Indians (9%), whereas in controls, Malays were high (42%) compared to Chinese (41%) and Indians (17%). From the retrospective analysis, ranibizumab was the most common (30.8%) drug used as a treatment for AMD, while PDT (84.4%) or combined therapy (58.2%) were used for polypoidal choroidal vasculopathy (a subtype of AMD) patients. A significant difference (P<0.05) was observed for the genotypic frequencies of VEGF +405 G/C, ARMS2 A69S, and HTRA1 -625 G/A gene polymorphisms when compared between AMD subjects and controls. However, the complement factor H (CFH) Y402H, complement component 3 (C3) R102G, VEGF -460 C/T and VEGF Insertion/deletion gene polymorphisms did not show any significant differences (P>0.05). The ARMS2 A69S and HTRA1 -625 G/A gene polymorphisms in response to the ranibizumab treatment among AMD subjects shows a significant association (P<0.05). Moreover, an over-expression of mRNA in the HTRA1 GG genotype was also reported and could contribute to the non-responders’ reaction to ranibizumab. However, no significant association (P>0.05) was observed in the CFH Y402H gene polymorphism with response to ranibizumab therapy based on both visual and anatomical outcome among AMD subjects. In conclusion,, Y402H, +405 G/C, A69S, 625 G/A polymorphisms of the CFH, VEGF, ARMS2 and HTRA1 genes, respectively, could be an independent risk factor and can be considered as a genetic susceptibility for the development of AMD among Malaysians.